Rotary blood-supplied patches for the treatment of osteomyelitis of the bones of the foot and the distal third of the tibia - V. V. Yurkevich; A. V. Pekshev; V. V. Podgornov (Бюллетень сибирской медицины, 2012)
The results of 112 transpositions of blood receiving complexes tissue foot applied in the treatment of chronic posttraumatic osteomyelitis of the bones of the foot and the distal third of the shin. Positive results were obtained in 86,6% of patients with recovery to work in 81,5% of the patients. The authors argue that the proposed blood receiving complexes tissue foot in the treatment of chronic posttraumatic osteomyelitis of the bones of the foot and the distal third of the shin allow to depart from the practice of multistage operations, reduce the time of hospital treatment. The algorithm for help in the treatment of chronic posttraumatic osteomyelitis of the bones of the foot and the distal third of the shin.